Pengaruh Akumulasi Modal, Pendidikan, Kreativitas dan Lokasi Usaha Terhadap Pendapatan Pedagang Perempuan - Paramita, Ayu Nyoman; Budhiasa, I Gede Sujana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
In this research will be found the effect of financial capital accumulation, the level of education, the creativity of labour and the trading location do to income of woman trader at Sukawati Art Market. This research used 80 kind of samples and use bootstrap method. Use primary data, the data gain, is analyzed previously by factor analysis, validity test and reliability test for creativity of labour ( X3) variable. The data had been collected is analyzed by path analysis. The result of research stated that financial capital accumulation variable, the creativity of labour, and the trading location give positif and significant impact do to income. Next the creativity of labour variable and trading location give positif and significant impact do to  variable the financial capital accumulation. And for the level of education variable give negative impact for the income and financial capital accumulation.
Keywords: The financial capital accumulation; the level of education; the creativity of labour; the trading location; income